(untitled) (SAARC Journal of Agriculture, 2022)
The study was aimed to evaluate the effect of different levels of carrot with ginger on the quality attributes of chicken nuggets. For this purpose, chicken meat samples were divided into four treatment groups viz. T0 (Control), T1 (1% ginger and 4% carrot), T2 (1% ginger and 8% carrot) and T3 (1% ginger and 12% carrot). Days of intervals were 0, 15, 30 and 45th days. Samples were preserved at -20º C for 45 days. An ANOVA of a 4×4 factorial experiment in completely randomized design having three replications per treatment was used for analyses of data. Sensory, proximate, physicochemical, biochemical and microbiological analyses were determined. Color, flavor, juiciness, tenderness and overall acceptability increased significantly (p<0.05) among the different treatment groups but decreased at different days of intervals. Dry matter (DM) content decreased significantly (p<0.05) with different treatment levels and increased with days of intervals. Crude protein (CP), Ether extract (EE) and ash content of all treatments were decreased significantly (p<0.05) among different treatment groups. Free fatty acids (FFAs), peroxide value (POV) and thiobarbituric acid reactive substances (TBARS) values were decreased significantly (p<0.05) with different treatment levels and increased with days of intervals. Total viable count (TVC), total coliform count (TCC) and total yeast mold count (TYMC) decreased significantly (p<0.05) at different treatments. On the basis of sensory, physicochemical, biochemical and microbial properties indicate that T3 was the best among treatment groups. Hence, 12% carrots with 1% ginger extracts may be recommended for formulation of value added chicken nuggets as enriched dietary fiber and natural antioxidant. SAARC J. Agric., 20(1): 185-196 (2022)